SISTEM PENJAMINAN MUTU PENDIDIKAN DALAM MENINGKATKAN MUTU PENDIDIKAN DI BPSDM PROVINSI PAPUA - Finansia Emilia Watungadha (Jurnal Darma Agung, 2022)
The“quality assurance system is a series of interrelated processes and systems in the activities of collecting, processing, analyzing, and reporting data related to the quality of teachers and other human resources in schools, programs and institutions.”“The education quality assurance process is an identification activity related to aspects of achievement, improvement, and the availability of data to plan and make decisions to help grow and develop a culture of improving the quality of education. LPMP was formed in order to assist local governments in the Papua region in terms of providing supervision, guidance, guidance, and technical services to education units at the Papua Province BPSDM as an effort to provide quality assurance for education units in the context of achieving national education goals. Widyaiswara BPSDM Papua Province carries out tasks and functions in improving the quality of education at BPSDM Papua Province through training, mapping the quality of education, mentoring, implementing, and evaluating the quality of education in the regions within the scope of BPSDM Papua Province